2004
DOI: 10.1007/s00705-004-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

L protein, the RNA-dependent RNA polymerase of hantaviruses

Abstract: L protein of hantaviruses is the RNA transcriptase and replicase that transcribes mRNAs and replicates the genomic RNA using antigenomic RNA as an intermediate. It also appears to have endonuclease activity. In this review, the current knowledge on the hantavirus L protein is presented including sequence motifs conserved in RNA polymerases, mechanisms of RNA synthesis and also the most recent findings on homologous RNA recombination and membrane association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 123 publications
1
53
0
Order By: Relevance
“…The mutation frequency in the PUUV L segment is higher than in the S and M segments (44). None of the mutations observed in this study are in the proposed functional domains of RdRp (27), and it remains to be shown whether these mutations in any way alter the enzymatic, or any other, function of RdRp.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The mutation frequency in the PUUV L segment is higher than in the S and M segments (44). None of the mutations observed in this study are in the proposed functional domains of RdRp (27), and it remains to be shown whether these mutations in any way alter the enzymatic, or any other, function of RdRp.…”
Section: Discussionmentioning
confidence: 56%
“…It remains to be shown whether the mutations observed in N protein and RdRp are connected to each other or not. Hantavirus RdRp is a large protein of approximately 250 kDa (26,27). Whether hantavirus RdRp has functions other than transcriptase and replicase activity is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction is supported by data from sex chromosomes (Berlin and Ellegren 2006;Wykoff et al 2002), mitochondrial genomes (Nachman et al 1994(Nachman et al , 1996Rand and Kann 1996) and Drosophila genomic regions with different recombination rates (Haddrill et al 2007). There is evidence of homologous recombination in DNA viruses (Thiry et al 2004;Wilkinson and Weller 2003) and in both positive strand (Agol 2006;Lukashev 2005;Twiddy and Holmes 2003;Worobey and Holmes 1999) and negative-strand (Hughes 2007;Kukkonen et al 2005;Spann et al 2003) ssRNA viruses. Nonetheless, it seems probable that, because of their compact genomes, RNA viruses have considerably higher rates of recombination per nucleotide site than those of many DNA viruses, particularly dsDNA viruses, whose genomes are much larger.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other segmented negative-strand RNA viruses, the hantavirus RdRp initiates transcription by a unique cap-snatching mechanism (17)(18)(19)(20)(21). Based on in slico analysis, the regions around amino acids 1 to 250 and 751 to 1290 have been proposed to constitute the capsnatching endonuclease domain and catalytic domain, respectively (22,23). The regions from amino acids 251 to 750 and 1291 to 2153 have not been assigned any function (Fig.…”
mentioning
confidence: 99%